Unusual Pharyngo-Esophageal Dysphagia Caused by a High-Riding Right Brachiocephalic Artery - Ki Hoon Park; Sora Baek; Eun Kyoung Kang (Annals of Rehabilitation Medicine, 2021)
High-riding right brachiocephalic and subclavian arteries are often asymptomatic and rare vascular variations. We present a patient with high-riding right brachiocephalic and subclavian arteries that caused compressive pharyngeal and cervical esophageal dysphagia. An 82-year-old woman presented to our hospital with dysphagia that worsened with solid food. A pulsatile lump was observed on the right neck side. A videofluoroscopic swallowing study showed a deviated food bolus movement anterolaterally from the normal vertical pharyngoesophageal transition, with a filling defect in the lower pharynx through the upper esophagus. Neck computed tomography (CT) showed high-riding right brachiocephalic and subclavian arteries and a tortuous right common carotid artery located adjacent to the trachea in the cervical area. The cervical midline structures were deviated to the left neck side. A neck mass with vascular variation should be considered as a cause of dysphagia that worsens with solid food; CT should be considered to determine its cause.